Kontribusi squat jump, leg squat, dan walking lunge terhadap kemampuan mawashi geri kicking - Indra Siregar, Yan; Nurkadri, Nurkadri; Rohaya, Nirwana; Muda, Sory; Alessandro Ginting, Delpipo (Universitas Nusantara PGRI Kediri, 2023)
Muscle explosiveness is a physical component that contributes from technical ability to karate ability. The kicking technique in karate is a very important skill in attacking movements. It is necessary to provide training so that muscle explosive power, especially in the legs, increases so that technical ability can increase. Squat jump exercises, leg squats, and walking lunges are forms of exercise that can increase muscle explosive power and the ability of karate kicks. This study aimed to determine the contribution of squat jump exercises, leg squats, and walking lunges to the ability to kick in karate. The subjects of this study were 27 female Karate Dojo athletes, the subject collection technique was total sampling by recruiting all 27 female athletes. The instruments used in this study were for initial and final test measurements using Mawashi Geri's kick ability test. Data analysis using ANOVA test and statistical prerequisite test using SPSS 25. The results of this study from the results of data analysis with a comparative hypothesis test between posttest values showed a calculated t value < a significant level of 0.05, which means that the provision of squat jumps, leg squats, walking lunges significantly contributed to Mawashi Geri's kicking ability. The conclusion of the results of this study explains that leg muscle power training has contributed to Mawashi Geri's kicking ability, especially in walking lunges training the results of the research are very significant.